2015
DOI: 10.1038/mtna.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Generation 2.5 Antisense Oligonucleotide Treatment Attenuates Doxorubicin-induced Nephropathy and Kidney Inflammation

Abstract: Preclinical and clinical data suggest CD40 activation contributes to renal inflammation and injury. We sought to test whether upregulation of CD40 in the kidney is a causative factor of renal pathology and if reduction of renal CD40 expression, using antisense oligonucleotides (ASOs) targeting CD40, would be beneficial in mouse models of glomerular injury and unilateral ureter obstruction. Administration of a Generation 2.5 CD40 ASO reduced CD40 mRNA and protein levels 75–90% in the kidney. CD40 ASO treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Preclinical and clinical studies have shown that the pro-inflammatory cytokine CD40 plays a crucial role in the onset and maintenance of the inflammatory reaction [14], and activation of CD40 contributes to renal inflammation and injury in vivo and in vitro [40, 41]. In the present study, TNF-α significantly increased CD40 expression at mRNA and protein levels in IMCD cells in a time- and concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…Preclinical and clinical studies have shown that the pro-inflammatory cytokine CD40 plays a crucial role in the onset and maintenance of the inflammatory reaction [14], and activation of CD40 contributes to renal inflammation and injury in vivo and in vitro [40, 41]. In the present study, TNF-α significantly increased CD40 expression at mRNA and protein levels in IMCD cells in a time- and concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 60%
“…The following groups were formed: control (no antisense oligonucleotide [ASO] treatment), ASO not specific to any murine transcript (ASO scramble ) and ASO SAA (specific for the murine Saa1 and Saa2 transcripts). Both ASOs are based on generation 2.5 chemistry, which consisted of 2-O, 4-C-[(S)-ethylidene]-D-ribose ('cEt') modified sugars for the three terminal 5′ and 3′ nucleotides that flank a central ten-nucleotide DNA gap [28]. The ASO treatment was performed via i.p.…”
Section: Methodsmentioning
confidence: 99%
“…While monoclonal antibody strategies encountered thrombotic complications, a late-generation antisense oligonucleotide approach has promise as an approach to limiting the action of this signaling dyad (102). A small molecule inhibitor of CD40 interaction with its signal transducing partner TRAF also holds interest in this regard (103).…”
Section: Beyond Cantos: Other Targets Other Indicationsmentioning
confidence: 99%